Classification of Human Driving Behaviour Images Using Convolutional Neural Network Architecture - Cengil, Emine; Cinar, Ahmet (Springer International Publishing Ag, 2019)
Traffic safety is a problem that concerns the worldwide. Many traffic accidents occur. There are many situations that cause these accidents. However, when we look at the relevant statistics, it is seen that the traffic accident is caused by the behavior of the driver. Drivers who exhibit careless behavior, cause an accident. Preliminary detection of such actions may prevent the accident. In this study, it is possible to recognize the behavior of the state farm distracted driver detection data, which includes nine situations and one normal state image, which may cause an accident. The images are preprocessed with the LOG (Laplasian of Gaussian) filter. The feature extraction process is carried out with googlenet, which is the convolutional neural network architecture. As a result, the classification process resulted in 97.7% accuracy.
14th International Conference on Hybrid Artificial Intelligence Systems (HAIS) -- SEP 04-06, 2019 -- Leon, SPAIN
Keywords: Convolutional neural networks; GoogleNet; Laplasian of Gaussian; Classification